Effect of pregabalin on postoperative pain and instrumentation-induced dysuria in patients undergoing percutaneous nephrolithotomy: A prospective randomized, double-blinded placebo-controlled study - Shivakrishna Choppa; Indira Gurajala; Prachi Kar; Kavitha Jayaram; Padmaja Durga; Rahul Devraj; Ramreddy Chilumula (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: The manipulation of urinary tract, the mandatory requirement of ureteral stenting, and bladder catheterization in patients undergoing percutaneous nephrolithotomy (PCNL) produces significant pain and dysuria postoperatively. The present study compared the efficacy of pregabalin with placebo in attenuation of these symptoms in patients undergoing PCNL. Material and Methods: This randomized controlled study was conducted in 110 patients of either sex, aged 18-65 years undergoing elective PCNL requiring nephrostomy tube under general anesthesia. Group G (n: 53) received pregabalin 150 mg and Group P received placebo (n: 49) orally 1 h before the anesthetic induction. All the patients received standard anesthetic protocol. Pain at the site of nephrostomy, instrumentation-induced dysuria (IID), anxiety, and sedation scores were recorded at 0 min, 15 min, 30 min, 1 h, 2 h, 4 h, 8 h, 12 h, 24 h postoperatively. Hemodynamics, total requirement of rescue analgesia, and incidence of any adverse effects were also noted. Results: Patients were demographically comparable between the two groups. There is no difference in nephrostomy site pain between the groups at different points of measurements. IID was less with pregabalin at 0 min, 15 min, 30 min, 1 h, and 2 h after extubation (P value < 0.05, 43% in Group G vs. 68% in group P). Severe urgency was seen in 4%, moderate in 31%, and mild in 33% of patients in placebo group. No patient in pregabalin had severe grade of instrumentation-induced dysuria score (P < 0.05). Patients in Group P required more rescue analgesic (P: 0.009). Anxiety scores, sedation scores, and hemodynamic parameters were comparable. Conclusion: A single dose of 150 mg pregabalin as oral premedication given 1 h before surgery reduced the incidence and intensity of IID compared to placebo in patients undergoing PCNL without significant adverse effects.